Strategic Adaptation and Sustainable Growth in Indonesia’s Medical Device Industry : A PESTEL-Based Conceptual Analysis of Industry Dynamics and Firm-Level Capabilities - Anggun Wida Prawira; Shifaun Qolbi (Program Studi Manajemen Bisnis Syariah, 2025)
Indonesia’s medical device industry has become a critical business phenomenon due to the simultaneous presence of market growth, import dependence, fiscal contraction, exchange-rate volatility and local content policy. This study aims to examine how medical device firms in Indonesia develop strategic adaptation and sustainable growth strategies under changing fiscal, regulatory and macroeconomic conditions. The study applies a descriptive qualitative-analytical method based on literature review, policy analysis, industry reports and recent academic studies. The theoretical framework integrates strategic market management, dynamic capabilities, market orientation, resource-based view and sustainable competitive advantage. The findings indicate that Indonesia’s medical device market continues to offer growth potential due to national health insurance expansion, public hospital procurement, primary-care strengthening and rising demand for diagnostic, monitoring and consumable products. However, the industry remains constrained by dependence on imported high-technology devices, exchange-rate exposure, selective public health spending and limited domestic production capability. Strategic adaptation is therefore required through sensing, seizing and transforming capabilities. Firms must strengthen regulatory capability, supply-chain resilience, value-based pricing, B2B-B2G relationship marketing, e-catalogue readiness, local production and after-sales service differentiation. This study contributes to strategic marketing literature by developing an integrated framework that connects external pressures, dynamic capabilities, accelerated marketing strategy and sustainable competitive advantage in an emerging healthcare market. Practically, the study recommends that Indonesian medical device entrepreneurs align business strategy with local content policy, procurement reform, financial resilience and healthcare-system sustainability.